2023
DOI: 10.2340/17453674.2023.5670
|View full text |Cite
|
Sign up to set email alerts
|

The European Bone and Joint Infection Society definition of periprosthetic joint infection is meaningful in clinical practice: a multicentric validation study with comparison with previous definitions

Abstract: Background and purpose: A new periprosthetic joint infection (PJI) definition has recently been proposed by the European Bone and Joint Infection Society (EBJIS). The goals of this paper are to evaluate its diagnostic accuracy and compare it with previous definitions and to assess its accuracy in preoperative diagnosis.Patients and methods: We retrospectively evaluated a multicenter cohort of consecutive revision total hip and knee arthroplasties. Cases with minimum required diagnostic workup were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…In a multicentre study of 697 revisions ( 56 ), the failure rate at 2 years after surgery was identical in cases with ≥2 positive cultures (17.9%), a single positive culture (17.0%) or culture-negative microbiology (17.2%), providing that the PJI was confirmed with the non-microbiological criteria in the EBJIS definition. This shows that EBJIS ‘confirmed’ culture-negative infections behave like EBJIS ‘confirmed’ culture-positive infections.…”
Section: The Elements Of the Ebjis Pji Definitionmentioning
confidence: 96%
See 3 more Smart Citations
“…In a multicentre study of 697 revisions ( 56 ), the failure rate at 2 years after surgery was identical in cases with ≥2 positive cultures (17.9%), a single positive culture (17.0%) or culture-negative microbiology (17.2%), providing that the PJI was confirmed with the non-microbiological criteria in the EBJIS definition. This shows that EBJIS ‘confirmed’ culture-negative infections behave like EBJIS ‘confirmed’ culture-positive infections.…”
Section: The Elements Of the Ebjis Pji Definitionmentioning
confidence: 96%
“…This question can also be addressed by using the clinical outcome as a ‘gold standard’ and correlating this with the diagnosis determined by each definition. In the multicentre study ( 56 ), it was shown that PJI diagnosis correlated closely with the outcome at 2 years, for all definitions (i.e. infected cases had a higher failure rate than non-infected cases).…”
Section: The Elements Of the Ebjis Pji Definitionmentioning
confidence: 98%
See 2 more Smart Citations
“…The EBJIS definition has been suggested to have increased sensitivity compared to previously proposed criteria, without negatively impacting specificity. It has also been showed to be better in preoperatively ruling out PJI when serological and synovial biomarkers yield negative results (Sigmund et al, 2022;Sousa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%